COPING MECHANISMS IN MEDICAL STUDENTS IN GENERATION Z: A SYSTEMATIC REVIEW - Mutiara Anissa; Al-Kindi Saga Rinaldi; Indah Salsabila; Sulistiana Dewi; Dian Budianti; Shinta Brisma (Yayasan Nusantara Hasana Berdikari, 2024)
Coping mechanisms are a person's efforts to overcome problems. Each person has different ways of dealing with problems, both positive and negative Coping. Using adaptive coping techniques will reduce the risk of getting stress, but maladaptive coping mechanisms will increase the risk of getting stress. To discover what coping mechanisms medical students in Generation Z use. Methods: This research was conducted using a systematic review method. Journal articles within the last five years were identified according to the topic. From the identification results, 20 relevant journals were found. No single coping mechanism works for everyone, but some adaptive coping mechanisms provide better health outcomes. The cause of many maladaptive coping mechanisms in Gen Z medical students is uncontrollable stress.